Hubungan antara Pembayaran Respons Pantas (QR) Mudah Alih dan Niat Tingkah Laku Pengguna dalam kalangan Generasi Y di UTHM - Ismail, Aiman Syazani; Kepal @ Nasir, Noreina (Research in Management of Technology and Business, 2023)
QR codes are used to store information about a product or individual identification information. Meanwhile, mobile QR payment is a contactless payment method where payment is made by scanning a QR code that has been prepared to be scanned and make payment. However, the acceptance rate of mobile QR payments in Malaysia is still low compared to other countries. Furthermore, most previous studies have not studied the factors of mobile QR payment usage among Generation Y, but among consumes without no age limit. Therefore, the objective of this study is to identify the relationship between mobile QR payments and consumer behavioral intentions among Generation Y at UTHM. The Theory of Technology Acceptance Model (TAM) was used in this study, aiming to evaluate the factors of mobile QR payment usage on consumer behavioral intentions. There are 4 factors stated in the theory, namely usefulness, ease of use, safety, and reliability. This study is focused on Generation Y groups aged 22 to 41 years old at UTHM who have used the mobile QR payment method. The sample for this study was 370, but in this study a total of 279 respondents were obtained. Using quantitative methods, questionnaires and online surveys were used. The data that will be obtained from the distributed questionnaire will be analyzed using Microsoft Excel and Statistical Processes for Social Sciences (SPSS). The results of the study found that mobile QR payment indeed helps Generation Y to shop for necessities and wants easily and the majority of users feel that they can rely on the mobile QR payment method. In summary, all four variables have a significant influence on the behavioral intention of users in the use of mobile QR payment at UTHM.